Interannual Variability of Energy and CO2 Exchanges in a Remnant Area of the Caatinga Biome under Extreme Rainfall Conditions - Mendes, Keila R.; Marques, Ana M. S.; Mutti, Pedro R.; Oliveira, Pablo E. S.; Rodrigues, Daniele T.; Costa, Gabriel B.; Ferreira, Rosaria R.; Silva, Any C. N. da; Morais, Leonardo F.; Lima, José Romualdo S.; Antonino, Antonio C. D.; Menezes, Rômulo S. C.; et al. (Sustainability, 2023)
Research focusing on energy, water vapor, and CO2 exchanges over the Caatinga Biome is recent. Consequently, there exist research gaps on this topic that limit our ability to understand and project interannual and long-term variations in the CO2 cycle of this environment. Thus, the objective of this study was to evaluate the behavior of the energy and CO2 balances of the Caatinga Biome under extreme rainfall conditions (extreme drought and intense rainfall) using simulations of the SITE model (Simple Tropical Ecosystem Model). Meteorological data from the years 2009 (heavy rainfall) and 2012 (extreme drought) obtained from an INMET automatic station were used. Relationships between monthly GPP and NEE values and rainfall were also analyzed. Although the SITE model had been previously calibrated for the region, adjustments to the calibration were necessary for our study due to the extreme climatic values of the selected years. The results highlight the impact of rainfall on energy and mass exchanges over the Caatinga, particularly evident in the partitioning of the energy balance and the CO2 balance. In 2009 (during heavy rainfall), the fraction of Rn converted into LE was nearly 6% higher compared to the values observed in 2012 (during extreme drought). Regarding CO2, it was found that the Caatinga behaved as a sink, even under extreme drought conditions (2012), with annual average values of −1.86 µmol m−2 s−1 (2009) and −0.81 µmol m−2 s−1 (2012). Relationships between monthly GPP and NEE values and rainfall were also investigated, revealing an asymptotic relationship between the components of CO2 balance and rainfall. It was evident that both the monthly values of GPP and NEE tend to stabilize when monthly rainfall volumes exceed 200 mm.